IMPLEMENTASI METODE AL-MIFTAH LIL ULUM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING KELAS I’DADIYAH DI PONDOK PESANTREN BAITURRAHMAN TASIKMALAYA - Doripah Niswah Elfida; Aja Rowikarim (HASBUNA : Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of implementing the Al-Miftah Lil Ulum method in improving the ability to read classical Islamic texts (kitab kuning) among I’dadiyah level students at Pondok Pesantren Baiturrahman Tasikmalaya. Using a descriptive qualitative approach, data were collected through observation, interviews, and practical reading tests, which included aspects of reading fluency, word class identification, nahwu and i‘rab analysis, determination of wazan and sighat, sequential translation (makna tartib), and mastery of nadzom. The findings reveal that 95% of the students successfully met the established competency standards. The effectiveness of this method is primarily supported by two factors: teacher capacity building through training at Pondok Pesantren Sidogiri and the implementation of a systematic evaluation standard. Accordingly, these results provide a significant contribution as a reference for the structured, efficient, and applicable implementation of kitab kuning learning methods within Islamic boarding schools (pesantren).